Pinukuik Kulit Pisang: Optimasi Pemanfaatan Hasil Pertanian Pisang Kepok di Sumatera Barat - Gusti, Utari Akhir; Wildayati, Wildayati; Ardi, Ardi (Jurnal Ekonomi Manajemen Perbankan, 2024)
West Sumatra is known as one of the largest banana producers in Indonesia, yet this potential has not been fully optimized. If maximized, it could have a positive impact on the community. Additionally, West Sumatra is famous for its diverse cuisine, including Pinukuik, which is becoming increasingly rare due to the high cost of ingredients. This research introduces "Pinukuik from Kepok Banana Peel" as a solution to optimize the use of kepok bananas. The data was collected through observation, interviews, questionnaires, and experimental analysis. The results show that 80% of respondents enjoyed the taste of Pinukuik made from banana peel, which contains 4.10% protein and 0.3169% calcium. Kepok banana peel is proven to be nutritious and suitable as a high-value food product. The production process is simple and cost-effective, making it easier to implement within the community.